2013
DOI: 10.1542/peds.2012-1197
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Screen Media Use Associated With Higher BMI in Young Adolescents

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Rates of screen media use have risen in parallel with rates of obesity among young people. Identifying the specific characteristics of media use that are associated with obesity can help elucidate the explanatory processes and inform effective interventions. WHAT THIS STUDY ADDS:This study examines the associations between BMI and characteristics of media use including the type of device, duration of use, and attention to the medium. The more that participants paid primary attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
2
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 43 publications
7
81
2
13
Order By: Relevance
“…Furthermore, diet quality was shown to mediate the association between time spent in sedentary behaviors and depressive symptoms [61]. Another possible explanation is that watching TV is relatively passive; watchers tend to pay more attention to TV compared with other screen uses such as video and computer, and attention to TV was associated with increased BMI [62]. However, we found that watching TV, screen time, and total sitting time all had the same association with BP.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, diet quality was shown to mediate the association between time spent in sedentary behaviors and depressive symptoms [61]. Another possible explanation is that watching TV is relatively passive; watchers tend to pay more attention to TV compared with other screen uses such as video and computer, and attention to TV was associated with increased BMI [62]. However, we found that watching TV, screen time, and total sitting time all had the same association with BP.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, a recent study reported that higher proportions of primary attention to TV, but not other media, were associated with higher adolescent BMI, 52 perhaps reflecting that the largest proportion of foodmarketing expenditures is still dedicated to TV. 53 Additionally, simultaneous eating may be easier while watching TV than while gaming, as one' s hands would be free of a controller/keyboard/ mouse.…”
Section: Figurementioning
confidence: 91%
“…Additionally, no studies to date have evaluated the effect of problem gaming on weight status. [30][31][32][33][34] Therefore, this study sought to determine the rate of problem gaming and its associated characteristics among children with obesity seeking care in PWM programs. Because problem gamers spend more time gaming, and thus potentially more time sedentary, and sedentary behaviors are associated with obesity, it is possible that one cause of obesity is problem gaming.…”
Section: Introductionmentioning
confidence: 99%